Дослідження процесу виготовлення паливних брикетів із біомаси - Болтянський, Борис Володимирович; Boltianskyi, Borys (Запоріжжя: ТДАТУ, 2025)
UA: Статтю присвячено дослідженню фізико-хімічних закономірностей процесу брикетування подрібнених деревних відходів. Проаналізовано роль природного полімеру – лігніну, який під впливом висо-кого тиску (145–150 МПа) та температури (100–110°C) переходить у пластичний стан, забезпечуючи фор-мування міцної монолітної структури брикету. Методологія дослідження ґрунтувалася на експериментах із варіюванням вологості сировини (від 4% до 12%) за сталих умов пресування. Отримані результати про-демонстрували, що залежність щільності брикету від вологості має нелінійний характер. Установлено, що оптимальна вологість сировини становить 8%, за якої досягається максимальна щільність (1,2 т/м³). Збіль-шення або зменшення вологості від цього значення призводить до зниження щільності брикету внаслідок утворення надмірної пари або недостатнього розм'якшення лігніну. Дослідження підтверджують, що визна-чення раціонального діапазону вологості є критичним етапом для створення високоякісного та енергоефек-тивного палива. /// EN: This article is devoted to a thorough study of the physicochemical patterns of the briquetting process of crushed wood waste. The work comprehensively analyzes the key role of the natural polymer lignin, which, under the influence of high pressure (145–150 MPa) and elevated temperature (100–110°C), transitions to a plastic state, thereby ensuring the formation of a strong monolithic briquette structure. This thermoplastic transition of lignin creates irreversible intermolecular bonds, which give the finished product the necessary water resistance and mechanical strength. The methodological basis of the study was based on a series of experiments with changes in the moisture content of raw materials in the range from 4% to 12% under constant pressing conditions. The results confirmed that the dependence of briquette density on moisture content is distinctly nonlinear. In particular, it was clearly established that the optimal moisture content of the raw material is 8%, at which the maximum density(1,2 t/m³) is achieved, which directly correlates with the calorific value. Deviations from this optimal value (both in the direction of increasing and decreasing moisture content) lead to a predictable decrease in briquette density due to the formation of excessive steam, which causes destruction of the structure, or, conversely, insufficient softening of lignin, which makes proper consolidation impossible. This convincingly proves that rational preparation of raw materials is a critically important stage in briquetting, as it affects both the quality and the specific energy consumption of the process. Thus, determining the optimal moisture range is a critically important step in creating high-quality and energy-efficient fuel that can meet international standards. The successful implementation of these scientifically based results in industry will significantly optimize production processes, reducing production costs, which is important for effective waste disposal and the development of circular economy principles.
Research on the process of manufacturing fuel bricks from biomass
Keywords: брикетування; деревні відходи; біопаливо; лігнін; вологість; тиск; щільність; термомеха-нічна активація; фізико-хімічні властивості; торрефікація; енергетична безпека; циркулярна економіка; briquetting; wood waste; biofuel; lignin; moisture content; pressure; density; thermo mechanical activation; physicochemical properties; torrefaction; energy security; circular economy